Profile of ICT Literacy Capability Using Rasch Model at SMP Negeri 2 Fakfak - Desi Ramadhanti; Rahmatullah Rahmatullah; Insih Wilujeng; Dian Septi Anifa Chusna (Indonesian Journal of Applied Science and Technology, 2021)
This research aims to determine learners' ability to solve ICT literacy problems by defining indicators, accessing, managing, combining, evaluating, creating, and communicating. The test was conducted on 24 learners spread across various classes in SMP Negeri 2 Fakfak. The instruments used in the study were 20 multiple-choice questions. This study is a descriptive study using Rasch models. The results showed that the average value of learners in solving defining problems is 49, accessing 27, managing, 18, combining 35, evaluating 20, creating 11, and communicating 15 with an overall average of 21.71 ± 14.62. Rach model shows learners 01L, 02L, and 18P have high intelligence while learners with the lowest ability are with code 07P, 12P, 09P, 08P, 05P, 13P, 14P, 16P, 19P, 21P, and 24P. The results showed that ICT literacy capabilities are still low, especially indicators of creation. This research can be used as a reference for teachers to continue to improve ICT literacy capabilities by doing learning innovation by optimizing the use of technology, communication tools, digital or the internet.